Translingualism as an Insight to Develop Academic Literacy in Foreign Language in Tertiary Education: A Literature Review - Esquicha Medina, Antonio (2022)
Academic literacy in a foreign language is a competence to be developed nowadays. However, approaches towards second language writing have traditionally been informed by monolingual perspectives, which reinforce the idea of a desired linguistic homogeneity with the native speaker as a referent. Translanguaging acknowledges the variety of backgrounds in current educational contexts, challenging the dominance of English as a target language within academic communities. Translingualism provides an ample comprehension of literacy practices occurring worldwide, where shuttling between codes is considered as evidence of linguistic repertoire instead of language interference. This literature review aims at describing contributions of translingualism to the development of academic literacy at tertiary level. Importance of L1 in the development of the writer’s identity, implications of translingualism in second language writing and multimodality and digital translingual practices are described as the main results reported in empirical research. To conclude, alternative insights towards academic literacy seem necessary to understand current literacy practices at university level when writing in a foreign language.